2021
DOI: 10.21273/jashs05077-21
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Underlying Color Variation in Calla Lily Spathes Based on Transcriptomic Analysis

Abstract: The calla lily (Zantedeschia hybrida) is a valued ornamental plant due to its unique shape and color variations. To determine the mechanisms responsible for color development in the calla lily spathe, we conducted a comparative transcriptomic analysis of the spathes of the black [Black Girl (B)], pink [Romantic (P)], and white [Ventura (W)] cultivars. The gene expression patterns in six spathe colors, including the preceding three colors as well as the amaranth [Promise (N)], red [Figo (F)], and yellow [Sun Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Xiong et al [ 34 ] performed a transcriptome analysis of variegated citrus plants and reported a Q30 score higher than 94.19%. In another study on the transcriptome of calla lily spathes, the GC content was between 50.5 and 51.05% [ 35 ]. Thus, the quality of the RNA-seq data in the present study was good for further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al [ 34 ] performed a transcriptome analysis of variegated citrus plants and reported a Q30 score higher than 94.19%. In another study on the transcriptome of calla lily spathes, the GC content was between 50.5 and 51.05% [ 35 ]. Thus, the quality of the RNA-seq data in the present study was good for further analyses.…”
Section: Discussionmentioning
confidence: 99%